Identifying essential genes in bacterial metabolic networks with machine learning methods - Kitiporn Plaimas; Eils, Roland; König, Rainer (BMC systems biology, 2010)
Identifying essential genes in bacteria supports to identify potential drug targets and an understanding of minimal requirements for a synthetic cell. However, experimentally assaying the essentiality of their coding genes is resource intensive and not feasible for all bacterial organisms, in particular if they are infective.
Gesehen am 03.05.2023